Utilising Plant Extracts as Lures to Capture Ambrosia Beetles (Coleoptera: Curculionidae) in Cocoa Plantation - Sylvia Sjam; Vien Sartika Dewi; Ade Rosmana; Asman; M. Bayu Mario; Elkawakib Syam’un; A. Amrullah; Syahribulan; Nuriadi; Nur Azizah Fitriyanti; Alim Nur Syafitri (Journal of Tropical Biodiversity and Biotechnology, 2025)
The ambrosia beetle (Coleoptera: Curculionidae) is a significant pest affecting cocoa plants in South Sulawesi. The high intensity of their attacks poses a serious threat to cocoa production, causing plants to wilt and die. This study developed traps baited with active ingredient compounds from various plant species, including coffee, carrot leaves, fermented cocoa wood, and eucalyptus oil, and compared their efficacy with ethanol. Beetles collected in these traps were identified based on morphological characteristics using a stereo microscope. The attraction test results indicated that all treatments successfully attracted ambrosia beetles, with ethanol capturing the highest number of individuals (1391). The results showed that ethanol and other extracts could capture ambrosia beetles of various kinds. The highest number of captures was found in ethanol and carrot leaf extract treatments. Additionally, eleven species were identified: Coccotrypes sp., Diuncus quadrispinulosus, Eccoptopterus spinosus, Hypothenemus sp. 1, Hypothenemus sp. 2, Hypothenemus sp. 3, Xyleborus affinis, Xylosandru s mancus, Xylosandrus crassiusculus, Xylosandrus eupatorii, and Xylosandrus morigerus. Traps baited with carrot leaf extract were most effective in capturing Hypothenemus sp. 3. These findings underscore the importance of developing various attractant traps utilising plant chemical compounds to detect and identify ambrosia beetle species and mitigate severe crop damage.